Rapid Detection and Identification of miRNAs by Surface-Enhanced Raman Spectroscopy Using Hollow Au Nanoflowers Substrates. (19th October 2017) - Cao, Xiaowei; Bao, Min; Shan, Yibo; Li, Wei; Shi, Hongcan
Abstract : MicroRNAs (miRNAs) are recognized as regulators of gene expression during the biological processes of cells as well as biomarkers of many diseases. Development of rapid and sensitive miRNA profiling methods is crucial for evaluating the pattern of miRNA expression related to normal and diseased states. This work presents a novel hollow Au nanoflowers (HAuNFs) substrate for rapid detection and identification of miRNAs by surface-enhanced Raman scattering (SERS) spectroscopy. We synthesized the HAuNFs by a seed-mediated growth approach. Then, HAuNFs substrates were fabricated by depositing HAuNFs onto the surfaces of (3-aminopropyl)triethoxysilane- (APTES-) functionalized ITO glass. The result demonstrated that HAuNFs substrates had very good reproducibility, homogeneous SERS activity, and high SERS effect. The substrates enabled us to successfully obtain the SERS spectra of miR-10a-5p, miR-125a-5p, and miR-196a-5p. The difference spectra among the three kinds of miRNAs were studied to better interpret the spectral differences and identify miRNA expression patterns with high accuracy. The principal component analysis (PCA) of the SERS spectra was used to distinguish among the three kinds of miRNAs. Considering its time efficiency, being label-free, and its sensitivity, the SERS based on HAuNFs substrates is very promising for miRNA research and plays an important role in early disease detection and prevention.